Dengue serotype-specific immune response in Aedes aegypti and Aedes albopictus - Smartt, Chelsea T (Instituto Oswaldo Cruz, Ministério da Saúde, 2017)

(untitled) (Mem Inst Oswaldo Cruz)
BACKGROUND: Dengue viruses (DENV) are considered one of the most important emerging pathogens and dengue disease is a global health threat. The geographic expansion of dengue viruses has led to co-circulation of all four dengue serotypes making it imperative that new DENV control strategies be devised. OBJECTIVES: Here we characterize dengue serotype-specific innate immune responses in Aedes aegypti and Aedes albopictus using DENV from Puerto Rico (PR). METHODS: Ae. aegypti and Ae. albopictus were infected with dengue serotype 1 and 2 isolated from Puerto Rico. DENV infected mosquito samples were collected and temporal change in expression of selected innate immune response pathway genes analyzed by quantitative real time PCR. FINDINGS: The Toll pathway is involved in anti-dengue response in Ae. aegypti, and Ae. albopictus. Infections with PR DENV- 1 elicited a stronger response from genes of the Toll immune pathway than PR DENV-2 in Ae. aegypti but in infected Ae. albopictus expression of Toll pathway genes tended to be similar between the serotypes. Two genes (a ribosomal S5 protein gene and a nimrod-like gene) from Ae. albopictus were expressed in response to DENV. MAIN CONCLUSIONS: These studies revealed a role for antiviral genes in DENV serotype-specific interactions with DENV vectors, demonstrated that infections with DENV-2 can modulate the Toll immune response pathway in Ae. aegypti and elucidated candidate molecules that might be used to interfere with serotype specific vector-virus interactions.